2002
DOI: 10.1002/jmv.10194
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of hepatitis A virus isolates from Buenos Aires, Argentina

Abstract: The Hepatitis A virus (HAV) has been classified in seven different genotypes, which include human (I, II, III, and VII) and simian (IV, V, and VI) groups. The sequence analysis of HAV strains contributes to the molecular epidemiology of the virus. Although the infection with HAV is endemic in Argentina and vaccination is being implemented in this country, using both IA and IB strains, there are very few data on the genotypes of the circulating viruses. On the basis of the sequences of 20 isolates collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 13 publications
3
29
1
Order By: Relevance
“…Phylogenetic analysis of the nucleotide sequence of the VP1/2A region of the HAV genome classified all isolates as genotype I, confirming former epidemiological data demonstrating that this is the main genotype circulating in Brazil (7,10,22) as well the most widespread genotype in the world (2,23,24). Additionally, we identified the simultaneous presence of sub-genotypes IA and IB in 65 and 35% of cases of HAV infection, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Phylogenetic analysis of the nucleotide sequence of the VP1/2A region of the HAV genome classified all isolates as genotype I, confirming former epidemiological data demonstrating that this is the main genotype circulating in Brazil (7,10,22) as well the most widespread genotype in the world (2,23,24). Additionally, we identified the simultaneous presence of sub-genotypes IA and IB in 65 and 35% of cases of HAV infection, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of sub-group IA in the tested samples is in line with our previous reports [13], in which sub-genotype IA was the predominant type in acute HAV infection. This sub-genotype was predominant in other countries such as Brazil, Cuba, Costa Rica, Argentina, and Thailand [2,10,11,20,23]. Other reports described the prevalence of sub-genotype IB Turkey [22].…”
Section: Discussionmentioning
confidence: 88%
“…Most of the human isolates have been found to belong to genotype I, in which subgenotype IA predominates over subgenotype IB. Previous studies have reported the occurrence of HAV subgenotype IA in Argentina, Brazil, Chile, Costa Rica, Cuba, El Salvador, and Uruguay [Robertson et al, 1992;Stene-Johansen et al, 1998;Arauz-Ruiz et al, 2001;Costa-Mattioli et al, 2001a;Diaz et al, 2001;Mbayed et al, 2002]. It has thus been suggested that the population of HAV circulating endemically in South America belongs to one subgenotype (IA) [CostaMattioli et al, 2001a].…”
Section: Discussionmentioning
confidence: 96%